The Persian version of Neurofibromatosis Type 1 Adult Health-Related Quality of Life (NF1-AdQOL) Questionnaire in Iranians: A Validity and reliability study - Reza Jahanshahi; Fatemeh Mirzaei; Mohammad Hossein Askari; Nafiseh Asgari; Shohreh Ghasemi; Akram Sanagoo; Leila Jouybari (Golestan University of Medical Sciences, 2023)
Background: Because of the numerous problems created by neurofibromatosis type 1, particular quality-of-life evaluation measures are quite significant. In Iran, general instruments are used to assess the quality of life of the target group. This study aimed to translate and examine the psychometrics of the Persian version of the Neurofibromatosis Type 1 Adult Health-related Quality of Life (NF1-AdQOL) questionnaire. Methods: This was a methodological and cross-sectional study. A total of 414 adult patients with neurofibromatosis type 1 in the Iranian Association of Neurofibromatosis were selected via convenience sampling. With the permission of the questionnaire's developer, the English version was translated into Persian using the standard back-translation procedure. Validity was assessed using face validity, content validity, exploratory, and confirmatory factor analysis. The reliability and internal consistency of the questionnaire were assessed by Cronbach's alpha and Spearman's correlation, respectively. Results: The participants' mean age was 34.48±8.3 years. The 31-item questionnaire was translated into Persian, and based on content validity analysis, 2 items were removed. The adequacy of the sample size was acceptable (KMO = 0.940). Exploratory factor analysis revealed 4 factors. The scale had good reliability (Cronbach's alpha: 0.95), and the intraclass coefficient was 0.91. The total mean quality of life score was 93±25.18. Conclusions: The finding showed that the Persian version of the questionnaire has good structural characteristics and is a reliable and valid instrument for measuring the quality of life of patients with neurofibromatosis 1.